Excessive Use of Nipah Leaf Membrane Cigarettes Increases the Severity of Spontaneous Pneumothorax: A Case study from Jambi, Indonesia - Dwinka Syafira Eljatin; Muhammad Ridho Akbar Eljatin; I Made Dwi Mertha Adnyana; Muhammad Bayu Zohari Hutagalung; Muhamad Frendy Setyawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Nipah (Nypa fruticans) is a type of palm that is widely used by the community. The local people of Jambi use Nipah leaves as a tobacco membrane for cigarettes. However, we found reports of cigarette use cases having implications for the severity of spontaneous pneumothorax disease. A 57-year-old man came to the emergency room suffering from shortness of breath, right-side chest discomfort, yellowish-green sputum cough, abdominal pain, nausea, weakness, decreased appetite, and inability to sleep. For two years, this man consumed ten Nipah membrane cigarettes he made independently daily, resulting in lung disease. The lungs were found to be asymmetrical with the weakened fremitus of the right lung stem; percussion revealed hyper resonance in the right lung and resonance in the left lung; auscultation revealed the presence of a decrease in vesicular breathing sounds in the right lung, and other breathing sounds crackling in both lungs. The patient's severe partially compensatory respiratory acidosis indicated levels of pH, pO2, pCO2, HCO3, total CO2, and BE. Sinus tachycardia, normoaxis and suitable atrial hypertrophy were found. The luscen region is visible, and the white line of the pleura on the right hemithorax shows the pneumothorax of the right lung. This case is relatively rare, and excess Nipah leaf membrane cigarettes increase the severity of spontaneous pneumothorax disease that causes COPD.